The Significance of a Trauma Survivor: The Representation of PTSD in HBO’s Game of Thrones - Desjardins, Kaila (Université d'Ottawa | University of Ottawa, 2019)
Mass media plays an important role in the dissemination of information regarding posttraumatic stress disorder (PTSD) and other forms of mental illness. The portrayal of characters with PTSD on television shows such as Game of Thrones (GoT) has the potential to deliver educational and therapeutic benefits; it is important for individuals who have not had exposure to the disorder to see others experience it, and watching someone go through trauma can help those who have lived through their own. While he has not been diagnosed, this paper postulates that GoT character Theon Greyjoy has PTSD, and it examines the representation of this illness in the popular television program. This postulation is based on Theon’s experiences and behaviours as well as on the five criteria identified for the diagnosis of PTSD outlined in the Diagnosis and Statistical Manual of Mental Disorders, fifth edition (DSM-V).
Keywords: PTSD; Game of Thrones